Geographical dimensions of the concentrations of gases polluting the air of the city of Basrah - Waleed Mustafa Suha (E3S Web of Conferences)
Air pollution is the most dangerous type of environmental pollution due to its easy spread over a wide area and because of its danger to population communities, the study aims to discuss the temporal and spatial dimensions of the concentrations of some gases polluting the air of the city of Basra (carbon monoxide CO. nitrogen dioxide NOx. sulfur dioxide So2, lead compounds Pb and Vocs volatile organic compounds) to identify the causes of air pollution, as 360 readings were taken distributed over (6) sites covering the study area comprehensively, and each site has 12 readings with 4 readings during one hour at a height ranging from (1.5-2) meters, taking into account the distance from direct sources of pollution during Recording the readings for the period from September (2021 to August 2022), the study reached a number of conclusions, including the high concentrations of polluting gases above the permissible environmental limits, the highest concentrations were recorded at the site (3). followed by the Site (6) and (1) due to the proximity to the sources of pollution represented by electric power plants, and the winter recorded the highest values of polluting gases.